STRATEGI KOMUNIKASI CALON LEGISLATIF MUDA PADA PEMILU DPRD KABUPATEN BANYUWANGI TAHUN 2024 - Izzul Haque Ash Shiddiqi; Leni Vitasari; Hary Priyanto (Yayasan Nusantara Hasana Berdikari, 2024)
Political communication strategy for young legislator candidates in the 2024 Banyuwangi Regency Regional People's Representative Council (DPRD) General Election to gain political legitimacy in the form of support and voting on election day. Young legislator candidates implement various patterns, including direct political outreach to the community, forming work teams or volunteers to carry out activities with the community, installing props, and contributing in the form of providing assistance according to community needs. This research using a qualitative approach aims to find out, describe and analyze the communication strategies implemented by young legislator candidates in the 2024 Banyuwangi Regency DPRD elections in order to gain public legitimacy. Based on the analysis of research findings, an effective political communication strategy through a systematic persuasive approach has the potential to open up opportunities for victory. Recommendations for innovative political communication by young legislative candidates are tailored to aspects: communication sources, communication messages, supporting channels or media, who is the target or recipient of political communication, and the effect of communication in the 2024 election contestation.